KETERBUKAAN INFORMASI PUBLIK UNTUK MENDUKUNG KINERJA ASN YANG BERKARAKTER DAN PROPORSIONAL - Laurensius Arliman S (JCH (Jurnal Cendekia Hukum), 2018)
State civil service (ASN) resource management is an important part of state governance that aims to assist and support all human resources of state civil apparatus to realize their full potential as civil servants and citizens. One is the openness of public information described in the UU ASN and the Law on Public Information Disclosure (UU KIP). The implications of the application of the KIP Law to the public or the public are the opening of access for the public to obtain information related to the public interest. First, Information that must be provided and announced and Required Information Announced necessarily (easy to reach and easy to understand). Establishing characterized and proportional ASNs are various ways, namely: 1) State Civil Service Committee (KASN); 2) Utilizing information communication technology (ICT), which provides public information disclosure data to the public through the website; 3) Implementation of UU KIP; 4) need to be socialized both to public bodies and communities; 5) Public bodies are given space to establish, build, and develop institutional PPIDs in accordance with the characteristics of institutions of their respective public bodies; 6) The government should be able to optimize socialization and encourage public participation to be able to carry out information disclosure, as mandated by UU KIP. With these means are expected to realize the character of ASN and proportional that also amandat of UU KIP.